A longitudinal, cross-lagged panel analysis of school absenteeism and symptoms of depression among economically disadvantaged adolescents - I Liu; Wei-Hsin Hung (International Journal of Adolescence and Youth)
The cross-sectional association between school absenteeism and depression has been identified in adolescents. However, the directionality, strength and stability of their temporal associations have been uncertain. The study was to explore the longitudinal association between the two phenomena in economically disadvantaged adolescents. We analysed data from the Taiwan Database of Children and Youth in Poverty, covering three waves over four years. A cross-lagged panel model was employed, consisting of four models built using a sample of individuals who were 13 years old at baseline. The paths from school absenteeism to later symptoms of depression were not significant, while the reverse paths from symptoms of depression to later absenteeism were significant. Prevention efforts should account for the unique longitudinal associations, particularly among economically disadvantaged students.